Haematological Changes in Guinea Fowls (Numida meleagris galeata, Pallas) Following Haemorrhage - Olayemi, F.O. (International Journal of Poultry Science, 2009)
Haematological changes associated with haemorrhage were determined in the guinea fowl (Numida meleagris galeata, Pallas). The red blood cell, packed cell volume and mean corpuscular haemoglobin decreased significantly (p<0.05) at 4 h post- haemorrhage and returned to normalcy one week after hemorrhage. After 4 h of hemorrhage, the haemoglobin concentration also fell significantly (p<0.05). The fall persisted the through the first week post-haemorrhage, it returned to normal value after 4 weeks of haemorrhage. The mean corpuscular volume was not affected for the first week after haemmorhage, but it fell significantly (p<0.05) at the fourth week of haemmorhage. The mean corpuscular haemoglobin was not altered by hemorrhage. This study showed that guinea fowls withstood 30% loss of blood and the haematological values were fully restored by the fourth weeks after haemorrhage.